MENYIAPKAN ALUMNI MERINTIS WIRAUSAHA KEBIDANAN DENGAN POSTPARTUM MASSAGE AND SPA ENTREPRENUERSHIP: MENGANTAR MIORI MENGGAPAI MIMPI (TAHUN KE III) - Nur Rahmawati, Rahajeng Siti; Rahmaningtyas, Indah; Titisari, Ira (Politeknik Kesehatan Kemenkes malang, 2025)
To address the discomforts experienced during the postpartum period, when mothers must adapt to their bodies returning to their pre-pregnancy state, along with adjusting to their new roles and the challenges of breastfeeding, several therapies can be undertaken. One such therapy is postpartum and lactation massage. In line with the vision of Kediri Midwifery Study Program Campus IV, which is